Optimal design and dynamic control of the HMDV inertial suspension based on the ground-hook positive real network. (September 2022) - Li, Yu; Yang, Xiaofeng; Shen, Yujie; Liu, Yanling; Wang, Wei
Highlights: The quarter-vehicle kinetic model of inertial suspension with the Switched Reluctance Motor (SRM) is established. The constraints of the first order and the second order ground-hook positive real networks are identified respectively. The first order and the second order ground-hook positive real networks structures are designed respectively. The paper combines the inertial suspension and the ground-hook control to achieve the reduction of the dynamic tire load at the wider frequency domain. The resonance peak of the dynamic tire load gain of the ground-hook positive real networks at low frequency band and at 5-10 Hz is reduced significantly and the performance of the second order ground-hook positive real network is better. Since the second order positive real network needs to be passively realized by using too many mechanical elements, the controller based on the Model Reference Adaptive Control (MRAC) is designed to control the mechatronic inerter to achieve the ideal performance output. Abstract: The positive real network of the inertial suspension system can effectively suppress the low frequency vibration of vehicle, but the improvement effect of it at medium and high frequency band is not significant. The ground-hook control can obviously reduce the vibration of the dynamic tire load at high frequency band. The motors of Hub Motor Drive Vehicle (HMDV) can increase the dynamic tire load, so the paper combines the inertial suspension and the ground-hook control to achieve the reduction of the dynamic tire load at the wider frequency domain. Firstly, the quarter-vehicle kinetic model with the Switched Reluctance Motor (SRM) is established. Then the constraints of the first order and the second order ground-hook positive real networks are identified, and the structural parameters are optimized respectively. In addition, the influences of the first order and the second order ground-hook positive real networks on the dynamic tire load are analyzed. Lastly, the controller based on the Model Reference Adaptive Control (MRAC) is designed to control the mechatronic inerter to achieve the ideal performance output. Simulation results show that, the Root Mean Square (RMS) values of dynamic tire load and suspension working space of the controllable inertial suspension is reduced by 18.21%, 28.26% respectively by comparing to the conventional suspension. And the dynamic tire load is suppressed at the wider frequency domain, which verify that the advantages of the inertial suspension and the ground-hook control are utilized effectively.